Moving visitation research forward: the Arizona prison visitation project : Essay/research commentary - Tasca, Melinda (Criminology, criminal justice, law & society, 2016)
Although the prison visitation literature is advancing in significant ways, it remains slowed by a reliance on a limited methodological approach. Here, we advocate for a new way to study visitation through the use of a mixed-method design. We discuss what knowledge can be gleaned by examining visitation differently and describe our efforts to do so by introducing a new data source: the Arizona Prison VisitationProject (APVP). This article outlines the methodology of the APVP and details the data collection process. We conclude with a discussion on how the APVP can be useful for guiding future research and policy.